Exploration of the oxygen reduction reaction activity of four transition metal borates: synthesis, structure and characterization. Issue 14 (13th March 2023) - Deng, Yan-Ling; Chen, An-Na; Li, Wei; Xin, Shu-Sheng; Pan, Chun-Yang
Abstract : Four new transition metal borates have been successfully synthesized. Borate-based catalysts were prepared at different temperatures and their electrocatalytic properties were explored. 1-CoB5/600 and 2-CoSB/450 exhibited ideal ORR activities. Abstract : Four new transition metal borates, [Co(1-MI)2 ]·B5 O7 (OH)3 (1, 1-MI = 1-methylimidazole), Co2 (PZ)8 (SO4 )2 ·2H3 BO3 (2, PZ = pyrazole), K7 {(BO3 )Co[B12 O18 (OH)6 ]}·H2 O (3 ) and K2 {[Ni(PY)2 ]2 ·[(C4 H2 O6 )2 B]}2 (4, PY = pyridine), have been successfully synthesized by a mild method. Their structures were determined by X-ray single crystal diffraction. These compounds were further characterized by FTIR, PXRD and UV-vis-NIR. It is worth noting that the catalytic properties of catalysts based on these four borates were explored, and that organically templated borate 1 - and 2 -based catalysts showed better ORR catalytic performance compared to 3 - and 4 -based catalysts. This may be caused by the supramolecular skeletons of 1 and 2 providing sufficient space and porosity.